2019
DOI: 10.3390/jcm8122165
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sacubitril/Valsartan on Clinical, Biochemical and Echocardiographic Parameters in Patients with Heart Failure with Reduced Ejection Fraction: The “Hemodynamic Recovery”

Abstract: Background: Sacubitril/valsartan has been shown to be superior to enalapril in reducing the risks of death and hospitalization for heart failure (HF). However, knowledge of the impact on cardiac performance remains limited. We sought to evaluate the effects of sacubitril/valsartan on clinical, biochemical and echocardiographic parameters in patients with heart failure and reduced ejection fraction (HFrEF). Methods: Sacubitril/valsartan was administered to 205 HFrEF patients. Results: Among 230 patients (mean a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
8
21
0
1
Order By: Relevance
“…Several retrospective studies reported similar results for LV reverse remodelling, which was observed in the early phase after ARNI treatment initiation. [17][18][19] In the present study, we observed significant improvements in LV function parameters in patients with HFrEF treated with ARNI, which is consistent with previous reports. Relevant echocardiographic parameters, including LV-EF, indexed LV volume, LAVI, mitral E/e′ ratio, PASP, and the severity of MR demonstrated concordant trends towards improvement.…”
supporting
confidence: 93%
“…Several retrospective studies reported similar results for LV reverse remodelling, which was observed in the early phase after ARNI treatment initiation. [17][18][19] In the present study, we observed significant improvements in LV function parameters in patients with HFrEF treated with ARNI, which is consistent with previous reports. Relevant echocardiographic parameters, including LV-EF, indexed LV volume, LAVI, mitral E/e′ ratio, PASP, and the severity of MR demonstrated concordant trends towards improvement.…”
supporting
confidence: 93%
“…Our study showed a significant improvement in patient’s quality of life, symptoms and functional status demonstrated by the reduction in the percentage of patients in NYHA class III and an increasing number of patients in NYHA class I and II at follow-up. Those results are aligning with previous studies, Romano et al [ 28 ] and other authors found a significant improvement in NYHA class after different interventions in patients with HFrEF [ 29 ]. The NYHA classification is the most commonly used system to describe the impact of heart failure on a patient's daily activities [ 30 ] and is recommended in all guidelines [ 10 , 15 ] as a useful tool to assess the functional limitations due to HF.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed a signi cant improvement in patient's quality of life, symptoms and functional status demonstrated by the reduction in the percentage of patients in NYHA class III and an increasing number of patients in NYHA class I and II at follow-up. Those results are aligning with previous studies, Romano et al [28] and other authors found a signi cant improvement in NYHA class after different interventions in patients with HFrEF [29] .…”
Section: Discussionsupporting
confidence: 93%